Presencia de Zeta mendozanum (Schrottky)(Hymenoptera: Vespidae) en Chile - Curkovic, T.=700 1 Barria, G.
(Es, En)
Ilus., 8 ref.
Keywords: HYMENOPTERA; VESPIDAE; IDENTIFICACION; REGISTRO; CHILE; AVISPAS; ZETA MENDOZANUM; REVISTA CHILENA DE ENTOMOLOGIA